Identification and functional characterization of SQSTM1/p62 and its importance in the autophagy process in Echinococcus granulosus - Lausero, Luciano Nicolás (2024)
Echinococcus granulosus is the causative agent of human cystic echinococcosis, a zoonotic infection endemic in many areas throughout the world. Once an individual is infected, this cestode forms metacestodes, which grow in host organs, thus, causing the disease. Identification of new drug targets is urgently required given the toxicity and poor efficacy of available drugs. The protein SQSTM1/p62 plays an important role in selective autophagy in different cellular systems, under stress situations as drug exposure, hypoxia and starvation. In this work we identified, re-named, and deposited in GenBank a putative orthologous gene of sqtsm1/p62 in E. granulosus (ID2837631), based on BLAST searches against the parasite genome (E-value cutoff 1e-25), the occurrence of conserved structural domains, and the transcriptional induction and in situ immunodetection under conditions of autophagy activation. The full-length open reading frame of Eg-p62 predicts a protein with 35% identity to the human ortholog (AAH01874 and Q13501), with a conserved domain structure containing the domains PB1 (homodimerization site with characteristic charged residues), ZZ (conserved amino-acids involved in autophagy regulation), IDR (binding sites for Raptor, LC3 and KEAP1) and UBA with ubiquitinated protein binding sites, allowing self-degradation and proteolysis of other ubiquitin-tagged proteins. By in totoimmune-localization assays and using autophagy-inducing-drugs such as rapamycin and hydroxychloroquine, we observed huge spherical aggregates (0.5-3 μm) around the nucleus in metacestodes and protoscoleces, and a positive signal in calcareous corpuscles and protonephridia. Inaddition, by qPCR analysis, we found that these drugs induced a two-threefold increase in Egsqstm1/p62 mRNA levels compared to untreated parasites. Here, we discuss the effects of Eg-p62 on the proteostatic status and aggrephagy in cestodes.